SISTEM AKUNTANSI SYARAT UTAMA DALAM BERWIRAUSAHA - ., Boedyo Supono (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2008)
ABSTRACT Â  Failure most off all from scale businessmen UKM because of 4 (four) factor namely : fund; effort management; skillfull human resources (SDM) and professional and also extension of marketing. To overcome the weakness before hand require to be woke up a system specially accounting system as main condition in managing company. Entrepreneurship is alternative of in reduction of unemployment and increasing of income to all actors. One of nature of personality to being owned by entrepreneurs is ability of organizational in understanding of can arrange purpose, orient responsibility and result to hard job. One form of responsibility relate to arrangement of finansial to be effective if applying accounting sytem matching with Indonesians accounting principles. Â  Keywords: accounting system, entrepreneurship.